El papel del editorialista en los procesos de integración: argumentación, pluralismo y consenso - Xamardo González, Nicolás (Estudios sobre el Mensaje Periodístico, 2007)
The editorialist has a fundamental performance in the communication of masses because he makes an essential function in the processes of integration of the citizenship in the society. The editorialist is a mediator daily in operations of consensus between the political power and the citizens for to form a favorable public opinion to the ideological interests that represent